VISUAL CONTENT OF THE OMNIBUS LAW DEBATE IN INDONESIA: A CULTURAL-HISTORICAL PERSPECTIVE - Lesmana, Maman; Lee Yeonkyung (International Journal of Cultural and Social Science, 2025)
This paper analyses forms of visual contents and their meanings from the perspective of a material cultural perspective to understand social media within the specifics of Indonesian contexts. Using intertextual theory, this study explores visual contents as artifacts and examines their meanings. The data collected through Twitter’s search functions (API) concerns the case of the Omnibus Law in Indonesia. The period of study ran from October to November 2020, when disputes between the pro-and anti- positions of controversy reached their peaks. The study concludes that specific historical, cultural, and social contexts exercise a significant influence on the preference of forms of visual contents; but when thinking about how messages are embedded in forms and conveyed to recipients, the choice of visual form is mainly dictated by ideological leanings, namely progressivism or conservatism.